Mechanical properties of soft clay stabilized with cement-rice husks (RH) - Mokhtar, Mardiha (2011)
Chemical stabilization has been extensively used for the improvement of soft clay soils, in enhancing the shear strength and limiting the deformation behaviours. Cement is widely used as a stabilizing material for soils, but the increasing price is causing economic concerns among practitioners and clients alike. The quest for alternative cheaper stabilizing agents is therefore more urgent than before. Rice husk is a major agricultural waste in Malaysia and the common disposal method of open burning has notoriously contributed to environmental pollution. The possibility of admixing rice husks with cement for stabilizing soft soils could be a solution to both problems. This study was aimed at assessing the usefulness of cement-rice husks as an effective soil stabilizer for improving the mechanical properties of clay soils. Laboratory experiments were carried out on a stabilized soft clay to study the inter-relationships between shear wave velocity, one-dimensional compressibility and unconfined compressive strength. Bulk clay samples were collected from the Research Centre for Soft Soils (RECESS) of UTHM. The stabilized specimens were prepared with the clay admixed with 5 % and 10 % cement and various quantities of rice husks, then compacted into cylindrical specimens measuring 38 mm in diameter and 76 mm high. The specimens were then left to cure for different periods up to a month. The stabilized specimens were observed to undergo increase in stiffness and strength, as well as significant reduction in compressibility, highlighting the great potential of cement-rice husk as an alternative soft soil stabilizer.